2020
DOI: 10.1038/s41598-020-60286-x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training results in depot-specific adaptations to adipose tissue mitochondrial function

Abstract: We assessed differences in mitochondrial function in gluteal (gSAT) and abdominal subcutaneous adipose tissue (aSAT) at baseline and in response to 12-weeks of exercise training; and examined depot-specific associations with body fat distribution and insulin sensitivity (S i). Obese, black South African women (n = 45) were randomized into exercise (n = 23) or control (n = 22) groups. Exercise group completed 12-weeks of aerobic and resistance training (n = 20), while the control group (n = 15) continued usual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 43 publications
0
37
1
Order By: Relevance
“…However, there are some indications in the literature for exercise-induced changes in adipose tissue mitochondrial respiration. Dohlmann et al (2018) found decreased mitochondrial respiration in subcutaneous abdominal adipose tissue in healthy men and women after 6 weeks of LV-HIT (18 HIT sessions with 7 × 1 min exercise bouts at ∼100% of VO 2 peak), while Mendham et al (2020) reported increased mitochondrial respiration in subcutaneous abdominal adipose tissue in black South-African women with obesity after 12 weeks of combined aerobic and resistance exercise training (4 days/week of 40-60 min with aerobic exercise at 75-80% HR peak and resistance training that included upper-and lower-body exercises at 60-70% HR peak ). We are not sure of the reasons for these divergent findings, but they may be explained by different exercise modalities and intensities.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some indications in the literature for exercise-induced changes in adipose tissue mitochondrial respiration. Dohlmann et al (2018) found decreased mitochondrial respiration in subcutaneous abdominal adipose tissue in healthy men and women after 6 weeks of LV-HIT (18 HIT sessions with 7 × 1 min exercise bouts at ∼100% of VO 2 peak), while Mendham et al (2020) reported increased mitochondrial respiration in subcutaneous abdominal adipose tissue in black South-African women with obesity after 12 weeks of combined aerobic and resistance exercise training (4 days/week of 40-60 min with aerobic exercise at 75-80% HR peak and resistance training that included upper-and lower-body exercises at 60-70% HR peak ). We are not sure of the reasons for these divergent findings, but they may be explained by different exercise modalities and intensities.…”
Section: Discussionmentioning
confidence: 99%
“…During excess food consumption, hyperglycaemia and elevated FFAs, the mitochondrial energetic efficiency and ROS production increase [26]. We recently showed that higher gSAT mitochondrial respiratory capacity was associated with higher gluteal fat accumulation in a cohort of African women [167]. Similarly, the resulting higher production of hydrogen peroxide correlated with lower insulin sensitivity in these women [167].…”
Section: Impaired Mitochondrial Functionmentioning
confidence: 96%
“…Of the 48 exercise sessions, participants attended 79 ± 13% (range 52-100%) at a mean intensity of 79.7 ± 4.0% (range 71-85%) HR peak [42]. There was no change in total habitual physical activity or sedentary time in response to the intervention (Table 1).…”
Section: Compliance and Participant Characteristics In Response To Thmentioning
confidence: 98%